Потеря массы атмосферы планеты WASP-195 b - Саванов, И. С.; Дмитриенко, Е. С.
The results of the estimations of mass loss from the atmosphere of the planet WASP-195 b are presented. The F type star WASP-195 has a planet with a mass of only 0.104 Jupiter masses, but with a radius comparable to RJup. The planet has a low density of p= 0.16 ± 0.06 g/cm3. To estimate the amount of outflow of matter from the planet's atmosphere, two approaches were used - an approximation formula corresponding to an energy-limited atmospheric loss model and a method based on the use of interpolation of the results for a grid of hydrodynamic models of the upper atmospheres. The values of the flux of XUV photons from the star were determined by an analytical dependence linking FXUV and the logR'HK parameter. The obtained estimates of mass loss from the planet's atmosphere for models of atmospheric loss with energy limitation and hydrodynamic approximation are compared depending on variations of the logR'HK parameter. Calculations have shown that the mass loss of the planet's atmosphere is quite large (even in the case of low stellar chromospheric activity). The maximum value of the parameter M can be 7.3 ·1011 g/s (hydrodynamic approximation model, high star activity).
Keywords: Звезды